The Emerging Nanoweapon of Orthopaedic Surgery. (Journal of Pakistan Orthopaedic Association, 2022)
Nanotechnology refers to the manipulation of structure and properties of materials at the nanometer scale(individual atoms ,molecule and supramolecular level) through biological, physical and chemical routes.1 This tiny alteration at the molecular level can cause a larger change. The surface area of nanoparticles ranges from 1 to 100nm and they demonstrate altered or enhanced biological response in contrast to particles with micrometer size surface area.2 The host organism tends to have different response to nanomaterials at cellular and protein level than shown for conventional particles.3 The concept of Nanotechnology was first introduced by Richard Feynman in 1959 and he is known as Father of Nanotechnology.4